Estimation of Photosynthetic Light Use Efficiency in Semi-Arid Ecosystems with the MODIS-Derived Photochemical Reflectance Index - Goerner, A; Reichstein, M; Rambal, S (Geoscience and Remote Sensing Symposium, 2008. IGARSS, 2008)
Direct estimations of light use efficiency from satellite data could reduce the uncertainties in data-oriented models of primary productivity. We analysed the potential of the photochemical reflectance index (PRI) based on MODIS data to approximate LUE of a Mediterranean Quercus ilex forest. Spectal band 1 (620-670 nm) turned out to be the best alternative reference band (the recommended 570 nm band does not exist on MODIS). Radiance correction with standard procedures (6S, dark object subtraction) did not improve the PRI-LUE relationship compared to the at-sensor reflectance version. The influence of surface anisotropy on the PRI signal was much reduced by constraining the observations to satellite data acquisitions with near nadir viewing angles.
Keywords: Drought; light use efficiency; photochemical reflectance index